Insomnia, hypersomnia and parasomnia in health university students (Research, Society and Development, 2023)
Objective: Determine the percentage of health students with complaints related to insomnia, excessive daytime sleepiness (hypersomnia) and parasomnia. Methodology: A quantitative, cross-sectional and descriptive study based on the Epworth Sleepiness Scale (ESS) and the Pittsburgh Sleep Quality Index (PSQI). The sample consisted of medical, nursing, physiotherapy, speech therapy and occupational therapy students from a public university in the state of Alagoas. Results: 252 students participated in the study. It was observed that 66.66% (n=168) of the students had poor sleep quality and 30.95% (n=78) had sleep disorders. About 34.52% (n=87) have moderate sleepiness and 18.65% (n=47) of students have severe sleepiness. Regarding parasomnias, 37.30% (n=94) of university students reported having had bad dreams during the night at least once a week. Conclusion: It is necessary for students to have support within the university for the management of identified complaints in order to enhance academic performance. Raising awareness about sleep hygiene can influence university students to recognize poor sleep habits that are interfering with academic performance.